A interferência fonológica do português L1 na aquisição de inglês L2 : os traços [+tenso] e [- tenso] - Assis, Alessandra Mara de (2008)
This dissertation tried to identify the interferences Brazilian Portuguese (BP) has in the acquisition of English as a foreign language, through a corpus made up of fifteen interviews with advance level students of English. This research had as an objective, to investigate the difficulties native speakers of BP find when learning English as a foreign language, mainly when it comes to the acquisition of the high front vowels, that can be long or short and have the features [+ tense] or [- tense], that is [i:] and [I] respectively. The other objective was to analyze the phonological processes involved in the manifestation of such vowels. In order to achieve our goals, we made use of some concepts of the following theories: The Distinctive Features Theory (Chomsky & Halle, 1968), The Syllable treatment pattern proposed by Selkirk (1982) and the syllable analyses to the BP proposed by Bisol (1999). For the BP Vowels we used the proposal of Câmara Jr. (1970) and for the English Vowels Chomsky & Halle (1968). As the last theoretical model we reached for The Optimality Theory McCarthy & Prince (1993), Kager (1999) and Prince & Smolensky (1993) in order to confront the grammar of both languages. The data gathering to build up the corpus was made through fifteen interviews with advanced students of English as a second language who are native speakers of BP and have learned English without leaving Brazil. After the data gathering we analyzed the data through a statistics program GOLDVARB (Windows). During the data gathering we could study perception and production of the target phonemes in different contexts getting to the following results: the context (preceding and following) in which the segment lies influences its correct perception and production, and the factor that most encourages the production of the long vowel with the feature [+ tense] is linguistic and is the lateral liquid /l/ in following context; BP interference in the acquisition of English as a second language provokes alterations in the syllable structure in L2 and if the teacher of English as a foreign language has formal knowledge in phonology he/she may make it easier for the scholar to learn English.